Streptococcus pyogenes and CAMP Positivity - Mesut YILMAZ (Flora Infeksiyon Hastalıkları ve Klinik Mikrobiyoloji Dergisi, 2002)
Group A streptococci (GAS) have long been considered CAMP negative. Moreover, the CAMP reaction has been commonly accepted as an important method to differentiate GAS from group B streptococci (GBS). During identification of beta-hemolytic streptococci in our laboratory, we have observed that GAS also produced a positive CAMP reaction. We here conclude that although CAMP reaction is one of the most important tests in presumptive identification of GBS, it should be questioned at this point with the review of relevant literature.